Tindakan Topikal Aplikasi Flour (TAF) di SD Tandang 01 Semarang - Retno Kusniati; Dwi Windu Kinanti; Nur Khamilatusy Solekhah; Hayyu Failasufa; Ayu Kristin Rakhmawati (Jurnal Abdimas Kesehatan (JAK), 2023)
Background: Dental caries is an infectious disease characterized by tooth decay or tooth decay. The main cause of dental caries is the bacterium Streptococcus mutans. Elementary school children aged 6-12 years are a group that is prone to caries due to deep pits and fissures on their permanent teeth. One of the most effective caries prevention efforts is the topical application of fluoride. Topical fluoridation is highly recommended for newly erupted children's teeth to strengthen the enamel layer and inhibit the demineralization process. Methods: Solving problems using methods including; counseling, tooth brushing together, and topical application of flour. Results: Students who participated in this activity consisted of 49% of students and 51% of elementary school students. The activity started with counseling about carien, brushing teeth together and finally giving Flour Topical Application. Conclusion: All students who met the dental health requirements were successfully given the Topical Flour Application